Combined effects of matrix and gene marker on the real‐time PCR detection of wheat. (25th May 2016) - Martín‐Fernández, Begoña; Costa, Joana; Oliveira, Maria Beatriz Prior Pinto; López‐Ruiz, Beatriz; Mafra, Isabel
Summary: DNA‐based methods have been advanced as excellent alternatives for the detection and quantification of gluten‐containing cereals. In this study, it was intended to evaluate the effect of three distinct food matrices on the performance three TaqMan real‐time PCR approaches targeting α2‐gliadin, agglutinin isolectin (Tri a 18) and thioredoxin h(Tri a 25) genes of wheat. The results of wheat flour detection in soya bean, maize and rice model matrices evidenced that sensitivity was considerably affected by both the food matrix and the target gene. Rice matrix allowed the highest sensitivity, in opposition to soya bean. The α2‐gliadin method enabled the best sensitivity, especially when combined with rice matrix (5 mg kg −1 ), followed by maize (10 mg kg −1 ) and soya bean (50 mg kg −1 ). These findings suggest that food matrix effects need to be carefully evaluated when developing real‐time PCR assays for wheat detection/quantification, but without compromising their great effectiveness as tools to monitor gluten‐containing cereals. Abstract : Wheat detection is affected by matrix and gene marker.